James M. Buchanan: from Chicago to Virginia and Knight's influence on Buchanan. (31st October 2018) - Forte, Francesco; Brady, Gordon L.
Abstract : This paper examines the influence of Frank Knight on James Buchanan during the latter's time as a student at the University of Chicago through to the successive periods of his life. We maintain that Knight's approach to economics and politics – in which individual freedom, (institutional) rules of the game and ethical rules are all paramount in explaining behaviours in both the market and the public sector – strongly influenced Buchanan's interdisciplinary intellectual enterprise. In this context, we stress Knight's influence on Buchanan's catallactic approach to both the formation of rules at the constitutional level and ordinary level, as well as for the behaviour of individuals interacting in the market and public sector. In this inheritance, the relevance of ethical values for economic progress and protection of a good, free society increased during Buchanan's last period of scientific research, with positive and normative levels always carefully distinguished, as in the Frank Knight tradition.